Male Pelvic Congestion and Erectile Dysfunction: Hidden Causes of a Clear Phenomenon in the Young - Nasrat, Abdullah M; Ahmed, Hassan A; El-Sayed, Salah M; Shabaka, Ahmed A; Nasrat, Mohammad M (Medical Science: Trends and Innovations Vol. 3, 2025)
Erectile dysfunction (ED) has an impact on the quality of life of both partners. Erectile function (EF), as a neurovascular phenomenon, is characterized by penile engorgement that results from local arousal-induced release of neuronal and endothelial-derived nitric oxide (NO). ED can arise from arterial etiology, venous leakage, or psychogenic reasons. The study aimed to demonstrate recent environmental reasons behind the rising phenomena of erectile dysfunction among young ages during recent decades. ED can be adequately prevented and improved by the reduction of cardiovascular disease risk factors, regular exercise, weight loss and abstinence from smoking. An apparent role for cytokines in the pathophysiology of ED has been emerging; this substance can induce vascular spasm and affect vascular endothelial function including endothelial-derived nitric oxide production (NO). The association of male pelvic congestion with the frequency of male sexual dysfunction has been documented in literature. As concerns therapeutic modalities, medicines work essentially by mediating or enhancing the effect of NO. ED is lately a common occurrence and its incidence is expected to increase significantly along with the increase in various lifestyle diseases. Colonic H. pylori strains were found frequently associated with pelvic congestion; H. pylori were considered as a possible underlying etiologic pathology in cases of pelvic pathology in general. The increased mucosal production of inflammatory cytokines of H. pylori could play an integral role in the pathogenesis of ED. The association of the colonic H. pylori strains with pelvic pathology, the role played by the inflammatory cytokines and the therapeutic effect of NO in ED were the scientific reasons to employ colon clear and blood-let out (BLO) cupping therapy in cases of ED. 40 patients with ED positive for colonic H. pylori strains were selected in two age groups; young and older age groups. They were scheduled for three sessions of colon clear, one each month, and a procedure BLO cupping therapy one week after the last colon clear. Marked improvement and most patients recovered their usual EF and sexual satisfaction. It was concluded that employment of combined colon clear and cupping therapy in cases of ED is promising and is not just hypothetical. Upon the basis of this combined traditional natural cure, most of the patients in the study have achieved satisfactory improvement.